The identity and taxonomic status of the generic names Schendylops Cook, 1899, and Schendylurus Silvestri, 1907, and the proposal of Orygmadyla, a new related genus from Peru (Chilopoda: Geophilomorpha: Schendylidae) - Hoffman, Richard L. (1997)
Fil: Hoffman, Richard L.. Virginia Museum of Natural History. Martinsville; United States